The Philosophy of Education Integrated in the English Module for Senior High School Entitled English Language Skill - Rochma, Anis Firdatul (Universitas Dian Nuswantoro, 2023)
Abstract. Teaching resources, such as textbooks and modules, play crucial roles in English language teaching. Thus, it is considered necessary to assess their contents in portraying the appropriateness with the English learning standards and criteria. However, most studies of printed teaching resources mainly focused on design and organization, grammar, vocabulary, language skills features, and practical organization. Those aspects are considered essential, yet the content analysis related to the philosophy of education is expected to be carried out as well since it holds several values that need to be embedded into English language teaching. Hence, the present study is projected to analyze the contents of the English module designed and created for the Senior High School grade X. This study utilizes the inferential type of content analysis. The data analysis discloses that the English module for Senior High School Grade X is recognized to incorporate three types of philosophy of education, namely pragmatism, existentialism, and progressivism. Each type of philosophy of education is considered able to develop the student’s English knowledge and skills. In addition, each philosophy of education incorporated in the English module is likely to assist the students in obtaining significant qualities for their future experiences.Keywords: contents; module; philosophy of education; teaching resourcesAbstrak. Sumber daya pembelajaran, seperti buku pelajaran dan modul, memainkan beberapa peran penting dalam pengajaran bahasa Inggris. Dengan demikian, dianggap perlu untuk menilai isinya dalam menggambarkan kesesuaian dengan standar dan kriteria pembelajaran bahasa Inggris. Namun, sebagian besar studi sumber daya cetak dicetak terutama berfokus pada desain dan organisasi, tata bahasa, kosa kata, fitur keterampilan bahasa, dan organisasi praktis. Aspek-aspek tersebut dianggap penting, namun analisis konten yang terkait dengan filsafat pendidikan diharapkan dilakukan juga karena memiliki beberapa nilai yang perlu dimasukkan ke dalam pengajaran bahasa Inggris. Oleh karena itu, penelitian ini diproyeksikan untuk menganalisis isi modul bahasa Inggris yang dirancang dan dibuat untuk kelas X SMA.Penelitian ini menggunakan tipe analisis konten inferensial. Analisis data mengungkapkan bahwa modul bahasa Inggris untuk Sekolah Menengah Atas Kelas X diakui untuk memasukkan tiga jenis filsafat pendidikan, yaitu pragmatisme, eksistensialisme, dan progresivisme. Setiap jenis filsafat pendidikan dianggap mampu mengembangkan pengetahuan dan keterampilan bahasa Inggris siswa. Selain itu, setiap filosofi pendidikan yang tergabung dalam modul Bahasa Inggris kemungkinan akan membantu siswa dalam mendapatkan kualitas yang signifikan untuk pengalaman masa depan mereka.Kata kunci: konten; modul; filosofi pendidikan; sumber daya pembelajaran